Home advantage in men`s and women`s Spanish first and second division water polo leagues - Prieto, J.; Gomez, M.-A.; Pollard, R. (Journal of Human Kinetics, 2013)
The purpose of this study was to quantify the home advantage in both men`s and women`s First and Second Division water polo leagues, to compare the results obtained according to sex of participants and the level of competition, and to test for possible differences in home advantage when considering the interaction between these two factors. The sample comprised four seasons from 2007-2008 to 2010-2011 for a total of 1942 games analyzed. The results showed the existence of home advantage in both men`s and women`s First and Second Divisions. After controlling for the competitive balance of each league in each season, there was a significant difference between men`s and women`s leagues, with higher home advantage for men`s leagues (58.60% compared with 53.70% for women`s leagues). There was also a significant difference between the levels of competition, with greater home advantage for the Second Division (57.95% compared with 54.35% for First Division). No significant differences in home advantage were found when considering the interaction between sex of participants and the level of competition. The results in relation to sex of participants and the level of competition are consistent with previous studies in other sports such as football or handball.